Queensland’s Abandoned Mine Land Program: improving the way we manage abandoned mines in Queensland - Stones, A.; Fogarty, K.; Grabski, A.; Hall, T. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
For over 150 years mining has played a significant role in the history of Queensland, Australia, and during that time many mines have been abandoned. These mines can pose significant hazards to community health and safety, and the environment. In recent years, the Queensland Government has significantly enhanced the management of abandoned mines through a series of policy, strategic and operational reforms. The Queensland Government enacted mine rehabilitation reform which included the release of a State Abandoned Mines Management Policy (the Policy), introduced the Financial Provisioning Scheme and amended legislation to authorise a broad range of remediation activities on abandoned mines. These reforms provided a platform for better management of existing abandoned mines and greater protection to the state from future abandonment. The Abandoned Mine Lands Program (AMLP) is a Queensland Government initiative to mitigate risk associated with approximately 120 high-risk abandoned mines. The AMLP is guided by the Policy, which aims to make abandoned mines safe, secure, durable through remediation and productive though recommercialisation and repurposing of sites in collaboration with our stakeholders. To assist in the delivery of the AMLP, the Queensland Government released the Risk and Prioritisation Framework for Abandoned Mine Management and Remediation (Department of Resources 2021a) (the Framework). The Framework sets out a transparent, robust, repeatable and risk-based approach to addressing hazards associated with abandoned mines. The Framework also considers the recommercialisation opportunities of the mineral waste material and/or unmined resources as well as a repurposing possibility. Based on the Framework, Wolfram Camp mine and the surrounding area were selected as a re-commercialisation pilot program in 2023. The aim of our paper is to distil the outcomes of the rehabilitation reform process and implementation of the Framework and Policy, and to provide an update of the deliverables from the AMLP. The information presented may be helpful in policy making and regulatory understanding.